Seroprevalence of human immuno-deficiency virus infection in babies born to HIV positive women - Nair, Atmaja; Vijaykumar, Bindu; R. Chandran, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Parent to child transmission (PTCT) is a major route of human immuno-deficiency virus (HIV) infection in children. PTCT contributes to about 4% of HIV infections in India. Prevention of parent to child transmission (PPTCT) of HIV involved testing of all pregnant women for HIV status, administration of antiretroviral therapy (ART) to HIV positive pregnant women, antiretroviral (ARV) prophylaxis to their infants and safe obstetric and infant feeding practices. Purpose of the study was finding out the mother to child transmission rates in our institution and whether we have been able to achieve the World Health Organization (WHO) target. Methods: This was a descriptive retrospective cohort study conducted in the Department of Obstetrics and Gynaecology, Government Medical College, Kozhikode, Kerala, India. Data of HIV positive mothers and infants born to them was collected using records. Results: Out of the 60 pregnancies, we had 23 new cases (40.3%) and 34 mothers (59.6%) known HIV positives becoming pregnant. 39.5% had taken ART for <24 weeks and 60.4% had taken ART for >24 weeks. There were 48 live births. At 6 weeks, 3 babies had tested positive by HIV total nucleic acid (TNA) polymerase chain reaction (PCR). One out of these expired at 1 week of diagnosis. Conclusions: Poor maternal adherence to ART, unsuppressed viral load, lack of ART during pregnancy, lack of ARV prophylaxis for the infant, poor antenatal visits were associated with HIV infections among children born to HIV positive mothers.